Devolución del impuesto al valor agregado en la economía familiar de las personas con discapacidad en el cantón Pallatanga, período 2022-2023 - Paguay Quishpe, Lizbeth Joana (2026)
This research aims to evaluate the Value Added Tax (VAT) refund on the household finances of people with disabilities in the Canton of Pallatanga during the period 2022- 2023. The study employed a qualitative approach with a field research design and an inductive research level. The target population consisted of 475 people with disabilities, from which a sample of 212 individuals was selected. Data were collected through a questionnaire. The Cronbach's alpha coefficient was 0.942. The results reveal a lack of awareness regarding VAT refunds for people with disabilities, leading to negative consequences for their household finances. Therefore, it was concluded that the population is not informed about this issue, indicating a deficiency in disseminating information about access to this tax right